Endothelial immunogenicity – A matter of matrix microarchitecture - Methe, Heiko; Hess, Shmuel; Edelman, Elazer R. (Thrombosis and Haemostasis, 2007)
The endothelium is a highly specialized active interface between blood and the underlying tissues, maintaining vascular tone, thrombo-resistance and selective permeability to cells and proteins. It is also an important regulator of inflammatory diseases, and endothelial-leukocyte interactions often herald complex diseases with an inflammatory component.Yet, the exact mechanisms promoting immune activation of endothelial cells (EC) are incompletely understood. Knowledge is accumulating that the immediate environment defines the cellular phenotype, whereby matrix composition and spatial formation (three- versus two-dimensional) seem to act as pivotal mediators. Here we summarize current findings denoting a key role of matrix environment in regulating endothelial immunogenicity. The immune response to three-dimensional matrix-embedded EC stands in stark contrast to the response engendered by injection of these same cells in their free state. Matrix-embedding confers a quiescent endothelial state with reduced expression levels of chemokines, adhesion, costimulatory, and major histocompatibility complex II molecules. Compared to EC grown on two-dimensional tissue culture plates, cytokine-stimulation of matrixembedded EC results in significantly reduced adhesion of natural killer cells and proliferation of co-cultivated allogeneicT cells. On the contrary, matrix-embedded EC induce an immune-inhibitory phenotype of dendritic cells and T regulatory cells to a greater extent than non-embedded EC. As vascular diseases are associated with profound changes in basement membrane composition and overall tissue architecture, our results indicate that the immediate environment of EC might play a pivotal role in initiating and regulating of different vascular diseases. Cell-matrix interconnections appear to govern endothelial immunogenicity and interactions between EC and immune cells.
Keywords: Endothelial cells; immunity; cell-matrix interactions